Flushing episodes in the context of frontal fibrosing alopecia with facial papules. Issue 8 (5th August 2021) - Bretas, Thales Lage Bicalho; Issa, Maria Claudia; Vargas, Thiago Jeunon; Sousa, Maria Auxiliadora Jeunon
Abstract : Frontal fibrosing alopecia (FFA) is a progressive frontotemporal hairline recession with eyebrow loss. Facial papules are present in up to 14% of FFA cases and can start with facial flushes. Nevertheless, these flushes are commonly associated with rosacea, a much more prevalent disease. In this case, a woman with FFA had, at first, clinical and histopathological findings of rosacea and was treated with ivermectin 1% cream with no improvement. She returned reporting new papules in the frontal region, reaching the frontotemporal hairline. Trichoscopy of the scalp showed mild perifollicular erythema and follicular scale. The new skin biopsy was compatible with FFA, and oral finasteride (5 mg/day) and hydroxychloroquine were introduced to stabilise the disease.